Psychosocial burden of beta-thalassaemia major in Antalya, south Turkey - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
beta-thalassaemia is a recessively inherited blood disorder characterised by chronic anaemia. It requires monthly blood transfusions and regular iron chelation. Thousands of affected children are born annually and the magnitude of the problem is most severe in developing countries. Ninety-nine children and 32 adults with thalassaemia major, and 112 parents of patients were interviewed in Antalya, south Turkey, using specifically designed questionnaires to evaluate psychosocial burden. The education of most of the thalassaemic children of school age (60%) was affected, mainly due to having to attend hospital for investigation and transfusions. A. high level of parental anxiety (82%) was reported. Nearly half of the families (47%) had employment and financial problems as a result of thalassaemia, yet there was a low level of marital breakdown (1.8%). A substantial majority (93%) of;the parental couples would have chosen to terminate an affected pregnancy if they had known that the foetus had thalassaemia major. The results reflect the need for a national policy for public education and screening of thalassaemia in Turkey in order to offer prenatal diagnosis for all families at risk of homozygous thalassaemia. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Turkey; beta-thalassaemia major; psychosocial burden; developing country; prenatal diagnosis; THALASSEMIA MAJOR; CHILDREN; INTEGRATION